Complexation of bovine serum albumin with cationic polyelectrolytes at pH 7.40 – Formation of soluble complexes. (October 2015) - Asimakopoulos, Theofanis; Staikos, Georgios
Abstract : Graphical abstract: Highlights: Complexes between BSA and a cationic polyelectrolyte, at pH = 7.40, in water and in 0.15 M NaCl. Soluble complexes between BSA and a cationic polyelectrolyte grafted with PDMAM, at pH = 7.40. Estimation of the molecular weight of the soluble complex formed by static light scattering. Abstract: Complexation of bovine serum albumin (BSA) with the cationic polymer poly([3-(methacryloylamino)propyl]trimethylammonium chloride) (PMAPTAC) and its graft copolymer with poly( N, N -dimethylacrylamide), (PMAPTAC- g -PDMAM75), was investigated at pH = 7.40, in water, and in 0.15 M NaCl, close to physiological conditions, as a function of the Polycation/BSA charge ratio, r . Turbidity, and UV absorption measurements, indicated the formation of insoluble stoichiometric complexes between BSA and PMAPTAC in water, but not in 0.15 M NaCl. A potentiometric study, in agreement with this behavior, showed proton release for the BSA/PMAPTAC mixtures in water, but not in 0.15 M NaCl. In the case of the mixtures of BSA with the graft copolymer PMAPTAC- g -PDMAM75, the solutions obtained even in water, were clear. Nevertheless, soluble complex formation in water was confirmed by potentiometry, ζ-potential and static light scattering measurements, while in 0.15 M NaCl not any complex formation was detected.